Buku4U : Sistem Kedai Buku SKBTR - Zariman, Hanie Amirah; Arbain, Siti Hajar (Applied Information Technology And Computer Science, 2026)
Buku4U: SBKTR Bookstore System is designed to address inefficiencies in the manual operations of Bandar Tun Razak 1 and 2 Primary School Bookstore. Buku4U system aims to help parents manage purchase online and simplify the process of picking up items at bookstore. By using HTML, CSS, JavaScript and MySQL programming language, Buku4U provides a user-friendly interface for efficient data management and interactive features to enhance the user experience. Buku4U was developed using the waterfall methodology. Key features include online ordering functionality, automated inventory management, and detailed sales reports, helping to improve operational efficiency. Buku4U not only speeds up the purchasing process but also ensures that inventory and booking records are always accurate. Lastly, this Buku4U contributes to improving operational efficiency and setting a benchmark for digial transformation in school bookstore.